Sub-crestal positioning of implants results in higher bony crest resorption: an experimental study in dogs - Cesaretti, Gianfranco; Lang, Niklaus P.; Salata, Luiz A.; Schweikert, Michael T.; Gutierrez Hernandez, Maria Elena; Botticelli, Daniele [UNESP] (Wiley-Blackwell, 2015)
To compare peri-implant soft- and hard-tissue integration at implants installed juxta- or sub-crestally. Furthermore, differences in the hard and soft peri-implant tissue dimensions at sites prepared with drills or sonic instruments were to be evaluated. Three months after tooth extraction in six dogs, recipient sites were prepared in both sides of the mandible using conventional drills or a sonic device (Sonosurgery(®) ). Two implants with a 1.7-mm high-polished neck were installed, one with the rough/smooth surface interface placed at the level of the buccal bony crest (control) and the second placed 1.3 mm deeper (test). After 8 weeks of non-submerged healing, biopsies were harvested and ground sections prepared for histological evaluation. The buccal distances between the abutment/fixture junction (AF) and the most coronal level of osseointegration (B) were 1.6 ± 0.6 and 2.4 ± 0.4 mm; between AF and the top of the bony crest (C), they were 1.4 ± 0.4 and 2.2 ± 0.2 mm at the test and control sites, respectively. The top of the peri-implant mucosa (PM) was located more coronally at the test (1.2 ± 0.6 mm) compared to the control sites (0.6 ± 0.5 mm). However, when the original position of the bony crest was taken into account, a higher bone loss and a more apical position of the peri-implant mucosa resulted at the test sites. The placement of implants into a sub-crestal location resulted in a higher vertical buccal bone resorption and a more apical position of the peri-implant mucosa in relation to the level of the bony crest at implant installation. Moreover, peri-implant hard-tissue dimensions were similar at sites prepared with either drills or Sonosurgery(®) .
Keywords: Sonosurgery; Animal study; Bone healing; Dental implants; Implant bed preparation; Implant dentistry; Osteotomy; Peri-implant soft tissue; Sub-crestal positioning